Komunikasi Bencana di Twitter: Studi Kasus Bencana Banjir Perkotaan di Daerah Khusus Ibukota (DKI) Jakarta` - Ahmad Maulana; Bevaola Kusumasari; Sri Rum Giyarsih (Universitas Gadjah Mada, 2021)
Social media occupies increasingly important roles in disaster response management. However, there are still doubts regarding the effectiveness of social media-based disaster communication. This paper aims to understand the discourse that emerge in Twitter containing facts or opinion regarding the flood disaster communication in DKI Jakarta under the different leadership of Basuki Tjahaja Purnama (2014- 2017) and Anies Rasyid Baswedan (2017-2020). This research used the methods of Corpus Assisted Discourse Study (CADS) and Actor Network Theory (ANT). These methods collected data on the discourse that is happening on Twitter and analyzes the network of actors who are active in discussions about floods in DKI Jakarta at different periods of leadership. This research found that the discourse that has developed on Twitter about floods in DKI Jakarta covers the personal problems of the leaders, the personality of the leaders, and the political position of the leaders, offered little messages that leads to solving the problem of flooding in DKI Jakarta. The active actor network is dominated by the local government of Jakarta as the responsibility holder or the main actor in delivering in information is only played by BPBD Jakarta.